Local Knowledge for Global Actions: The role of traditional ecological knowledge in climate change adaptation - Hosen, Nadzirah; Nakamura, Hitoshi (Environment-Behaviour Proceedings Journal, 2020)
The scale of climate change put indigenous people at higher risk than the others. Nonetheless, due to their intimate knowledge of their land, traditional ecological knowledge (TEK) held by the indigenous peoples may be the key to combating climate change. This article aims to explain the role that TEK plays in adapting to climate change. Document review included grey literature alongside peer-reviewed literature and project websites related to indigenous knowledge in climate change adaptation. The findings show that TEK not only helps indigenous people cope with environmental and climate pressures, but the knowledge system fosters resilience of socio-ecological systems. Keywords: climate change adaptation; Â traditional knowledge; traditional ecological knowledge; resilience eISSN: 2398-4287 Â© 2020. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/e-bpj.v5i13.2059